Integration of Folktale-Based Digital Comics to Improve English Language Skills for the Children and Youth Service Group of the Imanuel Oepura Congregation, Kupang City - Manafe, Novriani Rabeka; Huan, Elisna; Otta, Gracia M. N.; Rahayu, Gupuh; Arif, Muhammad; Kabelen, Alexander H.; Mogi, Gloria T.; Betty, Herlin J. (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service activity aims to improve English language skills and instill biblical values in children and adolescents at the Imanuel Oepura Congregation in Kupang City through the integration of digital comics based on folklore. This initiative was motivated by the urgency of mastering English in the era of globalization and efforts to preserve local wisdom. The implementation method involved 49 participants, where students delivered Sunday school material using digital comics that combined folklore with biblical values, followed by a quiz to evaluate understanding. The results of the activity showed a significant increase in children's engagement and understanding of the values conveyed. The developed digital comics have undergone expert validation tests (media, language, materials) with excellent percentages (e.g., 95.13% and 98.26% of trials, 100% by media experts, and 94% by language experts), confirming their quality and suitability as effective and engaging learning media. Positive responses from participants also indicate that digital comics have successfully increased reading interest and learning motivation. It was concluded that the integration of folklore-based digital comics is an effective method to increase engagement and understanding of the material, although the success of its implementation depends on the availability of supporting infrastructure. This activity is expected to be a reference for similar programs in the future in developing innovative and relevant educational media